Functional remodeling of perinuclear mitochondria alters nucleoplasmic Ca2+ signaling in heart failure. (10th June 2022) - Voglhuber, J; Holzer, M; Radulovic, S; Thai, PN; Djalinac, N; Matzer, I; Wallner, M; Bugger, H; Zirlik, A; Leitinger, G; Dedkova, EN; Bers, DM; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): BioTechMed-Graz Mitochondrial dysfunction in cardiomyocytes is a hallmark of heart failure (HF) development. Although initial studies recognized the importance of different mitochondrial subpopulations, there is a striking lack of direct comparison of intrafibrillar (IF) vs. perinuclear (PN) mitochondria during the development of HF. Here, we use multiple approaches to examine the morphology and functional properties of IF vs. PN mitochondria in pressure overload-induced cardiac remodeling in mice, and in non-failing and failing human cardiomyocytes. We could demonstrate that PN mitochondria from failing cardiomyocytes are more susceptible to changes in mitochondrial membrane potential (ΔΨm), ROS generation and impairment in Ca2+ uptake compared to IF mitochondria at baseline and under physiological stress protocol. We also demonstrated, for the first time, that under normal conditions PN mitochondrial Ca2+ uptake shapes nucleoplasmic Ca2+ transients (CaTs) and prevents nucleoplasmic Ca2+ overload. Loss of PN mitochondria Ca2+ buffering capacity translates into increased nucleoplasmic CaTs and may explain disproportionate rise in nucleoplasmic [Ca2+] in failing cardiomyocytes at increased stimulation frequencies. Therefore, a previously unidentified benefit of restoring the mitochondrial Ca2+ uptake may be normalization of nuclear Ca2+ signaling and alleviation of altered excitation-transcription, which could be an important therapeutic approach to prevent adverse cardiac remodeling.